Coaching Winning Model United Nations Teams : A Teacher's Guide - Mickolus, Edward F.; Brannan, Joseph (Book collections on Project MUSE., 2013)
By some counts, Model United Nations (MUN) has become the single most popular extracurricular academic activity among high school students. More than two million high school and college students have assumed the roles of ambassadors from real United Nations member countries, participated in spirited debate about the world's most pressing issues, and called, "Point of order, Mr. Chairman!" Now, in Coaching Winning Model United Nations Teams, Ed Mickolus and J. Thomas Brannan give MUN teachers and coaches the information they need to succeed. In this informative volume, the authors (MUN coaches themselves) provide detailed guidance for each step of the MUN path, from the first meeting in the teacher's classroom to the final days of an official MUN conference. Coaches will learn about the ins and outs of parliamentary procedure and the most effective ways to help their students draft position papers and resolutions. Most important, Mickolus and Brannan illustrate the many ways that teachers can inspire their students to take an active role in making the world a better place. By the time their students move on, MUN coaches will have instilled in them such important qualities as empathy, self-confidence, and grace under pressure. Coaching Winning Model United Nations Teams is a fun, useful guide for teachers and coaches who are working to help develop tomorrow's leaders today.